A Plausible Link of TMPRSS2/ACE2/AR Signaling to Male Mortality during the COVID-19 Pandemic in the United States - Lilly M. Wong (MDPI AG, 2021)
The COVID-19 pandemic continues around the world, where the United States is among the worst in terms of both morbidity and fatality of the viral infection. We aim to investigate the plausible link of tissue SARS-CoV-2 viral entry gene expression, such as TMPRSS2 and ACE2, with infection and death by gender during the COVID-19 pandemic in the United States. We find a significantly higher incidence of COVID-19 death in men than in women, even though SARS-CoV-2 infection in women is higher than in men. We discover that the expression of TMPRSS2 and ACE2 in intestine, but not in lung, tends to be positively associated with the incidence of SARS-CoV-2 infection in men. In contrast, the high incidence of death in men is negatively correlated with TMPRSS2/ACE2 expression in intestine. Strikingly, the correlation of TMPRSS2/ACE2 expression with SARS-CoV-2 infection and death is the opposite in females, compared with that in males. Interestingly, male hormone signaling seems to be involved in mortality, as the low expression of testosterone receptor AR in the prostate contributes to death in men according to age. These observations point to a plausible contribution of male hormone metabolism in the regulation of TMPRSS2/ACE2 signaling to fatality by SARS-CoV-2 infection in men.